Frequency of hypoferritinemia, iron deficiency and iron deficiency anemia in outpatients - Akarsu, Saadet; Kilic, Mehmet; Yilmaz, Erdal; Aydin, Mustafa; Taskin, Erdal; Aygun, A. Denizmen (Karger, 2006)
The prevalence rates of hypoferritinemia (IDec/one abnormal indicator), iron deficiency (IDef/two abnormal indicators) and iron deficiency anemia (IDA) in children who were referred to the outpatient clinics of the Department of Pediatrics for the first time within 1 month were investigated. Exclusion criteria were iron therapy before and during the study period and a history of chronic illness. Acute-phase reactants, such as erythrocyte sedimentation rate and C-reactive protein levels, were measured in all cases indicative of infectious diseases. Blood samples were obtained from each study patient admitted to the outpatient clinics during the study period. The hospital charts were later further evaluated, and samples of patients with any current illness known to interact with the iron status of the patient were discarded, and patients were contacted to supply new samples about 1 month after treatment of the infection. Thus, in patients with indications of an infection, samples obtained 1 month after treatment were assessed. The children (n = 557) were divided into four age groups: those aged 4 months to 2 years (group I), 2-6 years (group II), 7-12 years (group III) and 12-18 years (group IV). Children with a decrease in serum ferritin levels without anemia (IDec), and those with lower ferritin, transferrin saturation (TS) and serum iron (SI) concentration (IDef) were evaluated. IDA was diagnosed if hemoglobin (Hb) concentrations were lower than those adjusted for age, ferritin < 12 ng/ml and TS <= 16% and if Sl was decreased. IDec, IDef and IDA were detected in 26, 11.1 and 12.7% of the patients, respectively. Only 50.1% of the patients visiting the outpatient clinics were found to be normal. The rates of IDec (28.9%), IDef (21.9%) and IDA (26.2%) were highest in group I. IDec had the highest percentages in all groups. In group I, the rates of IDec, IDef, and IDA were 37.2, 66.1 and 69%, respectively. Sl concentration was abnormal in 77.1% of the cases in group I (4 months to 2 years of age). Half of the patients referred to the outpatient clinics were suffering from abnormalities related to lower SI concentrations. Close monitoring and treatment of iron deficiency is advised especially in early childhood. Copyright (c) 2006 S. Karger AG, Basel
Keywords: childhood; hypoferritinemia; iron deficiency anemia; supplementation, iron